Vulnerability assessment and seismic mitigation intervention for artistic assets: from theory to practice. (15th July 2018) - Baggio, Sebastiano; Berto, Luisa; Rocca, Irene; Saetta, Anna
Highlights: Seismic vulnerability assessment of artistic assets is studied, aiming at exploiting the potential of specifically designed seismic-isolation strategy. Different approaches to evaluate the filter-effect of the host building in the evaluation of the seismic action are critically investigated. Operative tools are proposed to support the design phase of seismic device. An emblematic case study is selected and analysed following an interdisciplinary methodology leading to the design of an effective seismic mitigation intervention. Transition from theory to practice is a key aspect which gives a contribution on how to address similar issues in preserving artistic objects from earthquake damage. Abstract: This paper deals with the vulnerability assessment of artistic assets, aiming at exploiting the potential of specifically designed seismic-isolation strategy to mitigate their seismic risk. In detail, starting from a review of the multidisciplinary procedure proposed by some of the authors for evaluating the safety level of art objects, this paper focuses on the required steps necessary to effectively design proper seismic mitigation intervention. For this purpose, the case study of the bust of Francesco I d'Este is investigated. This sculpture is housed at the second floor of Palazzo dei Musei in Modena, one of the cities hit by the seismic events occurred in May 2012 in Italy, which brought up to date the need of preserving this valuable object from seismic risk. After a preliminary vulnerability analysis carried out to assess the safety of the bust, a specific intervention of seismic isolation is conceived and realized by adopting Double Concave Curved Surface Sliders (DCCSS), which combine a strong flexibility to different museum contexts, with the possibility of standardizing the production process. To this aim, some operative charts are proposed as useful tool for the design phase of the seismic devices. Then special attention is devoted to an accurate evaluation of the seismic action, considering the location of the artistic asset at upper floors, also by means of different strategies for numerical modeling of the host masonry building. Finally, a series of non linear dynamic analyses are carried out to assess the effectiveness of the whole isolated system.